A note on the discontinuity stresses at the junction of a pressurised spherical shell and a cylinder - Houghton, D. S.; Chan, A. S. L. (College of Aeronautics, 1958)
An analysis has been made of the forces and moments occurring at the junction of a pressurised spherical shell with an intersecting cylinder. The additional effects of having a temperature gradient along the length of the cylinder and the effect of a jointing ring have been considered.